The concept of "void contract" in public procurement (Law and Safety, 2021)
The way of origin and consolidation in the public procurement procedure of the institute of a void contract, which was first formulated as "the result of invalid bidding", is analyzed.The scientific developments devoted to the issues of voidence of transactions and scientific research in the field of public procurement in Ukraine are summarized.The author's definition of the procurement contract is given: it is an agreement between the Customer and the Participant (more parties), aimed at establishing, transferring or terminating property rights and obligations, which is concluded as a result of the procurement procedure and provides for ownership of property services or works.The grounds for declaring the procurement contract null and void are listed, namely: concluding a procurement contract before or without the procurement procedure, concluding a procurement contract that differs from the content of the tender offer / offer based on the results of the electronic auction; concluding an agreement during the period of appealing the procurement procedure to the Antimonopoly Committee of Ukraine; concluding a contract in violation of the terms.The main conceptual differences between a void contract in public procurement and the civil law doctrine of a void transaction are established and characterized. The main difference from void transactions is that the parties and third parties do not have to obtain a court decision to apply the consequences of declaring a transaction invalid, but in cases established by the Civil Code of Ukraine, a void transaction may be recognized by a court as valid.The notion of "void contract" in public procurement is critically analyzed through the prism of understanding and essential conditions of general civilization of invalid contract, as it is not possible to recognize such a contract valid in court.The definition of a void contract in public procurement as one that violates public order, is concluded in violation of the procedure provided by law, and makes it impossible to recognize it valid in court.
Keywords: tender; public procurement; contract; procurement contract; essential terms of the procurement contract; voidence of the procurement contract.